Causality of small and large intestinal microbiota in weight regulation and insulin resistance - Torsten P.M. Scheithauer; Geesje M. Dallinga-Thie; Willem M. de Vos; Max Nieuwdorp; Daniël H. van Raalte (Elsevier, 2016)
Objective: The twin pandemics of obesity and Type 2 diabetes (T2D) are a global challenge for health care systems. Changes in the environment, behavior, diet, and lifestyle during the last decades are considered the major causes. A Western diet, which is rich in saturated fat and simple sugars, may lead to changes in gut microbial composition and physiology, which have recently been linked to the development of metabolic diseases. Methods: We will discuss evidence that demonstrates the influence of the small and large intestinal microbiota on weight regulation and the development of insulin resistance, based on literature search. Results: Altered large intestinal microbial composition may promote obesity by increasing energy harvest through specialized gut microbes. In both large and small intestine, microbial alterations may increase gut permeability that facilitates the translocation of whole bacteria or endotoxic bacterial components into metabolic active tissues. Moreover, changed microbial communities may affect the production of satiety-inducing signals. Finally, bacterial metabolic products, such as short chain fatty acids (SCFAs) and their relative ratios, may be causal in disturbed immune and metabolic signaling, notably in the small intestine where the surface is large. The function of these organs (adipose tissue, brain, liver, muscle, pancreas) may be disturbed by the induction of low-grade inflammation, contributing to insulin resistance. Conclusions: Interventions aimed to restoring gut microbial homeostasis, such as ingestion of specific fibers or therapeutic microbes, are promising strategies to reduce insulin resistance and the related metabolic abnormalities in obesity, metabolic syndrome, and type 2 diabetes. This article is part of a special issue on microbiota.